Quality of employment in small firms - Cristian UȚĂ (Journal of Economic Development, Environment and People, 2018)
The strategic objective of the European Union set out in Lisbon is to become the most competitive and dynamic knowledge-based economy capable of delivering sustainable economic growth, increasing employment and developing greater social cohesion. At the heart of this strategy are businesses, and given that the vast majority of them are SMEs (less than 250 employees), policies to achieve this are focused on them. At the same time, improving the quality of work and working conditions is still an important objective on the European political agenda due to multiple socio-economic implications. In this context, the work "Quality of Employment in Small Companies" by Daniela Paşnicu and Gabriela Tănase is very current. Appeared in 2017 at the University Publishing House, the paper is structured in five chapters.